The sexual and ontology - Zupančič Alenka (Filozofija i Društvo, 2014)
This paper explores some of the crucial ontological implications of the psychoanalytic theory of sexuality in its Freudo-Lacanian orientation. As irreducible to different sexual practices and contents, the concept of sexuality obtains conceptual weight that makes it particularly relevant for philosophical ontological thinking. Starting from the hypothesis that something about sexuality is constitutively unconscious - that is to say, existing only in the form of the unconscious - the paper points at the singular short-circuit of the epistemological and ontological level which is at work in psychoanalytic theory, and which cannot be neglected in philosophical examination of the relation between knowledge and being.